A compendium answering 150 questions on COVID-19 and SARS-CoV-2 - Riggioni, Carmen; Comberiati, Pasquale; Giovannini, Mattia; Agache, Ioana; Akdis, Mübeccel; Alves-Correia, Magna; Antó, Josep M; Arcolaci, Alessandra; Azkur, Ahmet Kursat; Azkur, Dilek; Beken, Burcin; Boccabella, Cristina; et al. (Allergy, 2020)
In December 2019, China reported the first cases of the coronavirus disease 2019 (COVID-19). This disease, caused by the severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2), has developed into a pandemic. To date, it has resulted in ~9 million confirmed cases and caused almost 500 000 related deaths worldwide. Unequivocally, the COVID-19 pandemic is the gravest health and socioeconomic crisis of our time. In this context, numerous questions have emerged in demand of basic scientific information and evidence-based medical advice on SARS-CoV-2 and COVID-19. Although the majority of the patients show a very mild, self-limiting viral respiratory disease, many clinical manifestations in severe patients are unique to COVID-19, such as severe lymphopenia and eosinopenia, extensive pneumonia, a "cytokine storm" leading to acute respiratory distress syndrome, endothelitis, thromboembolic complications, and multiorgan failure. The epidemiologic features of COVID-19 are distinctive and have changed throughout the pandemic. Vaccine and drug development studies and clinical trials are rapidly growing at an unprecedented speed. However, basic and clinical research on COVID-19-related topics should be based on more coordinated high-quality studies. This paper answers pressing questions, formulated by young clinicians and scientists, on SARS-CoV-2, COVID-19, and allergy, focusing on the following topics: virology, immunology, diagnosis, management of patients with allergic disease and asthma, treatment, clinical trials, drug discovery, vaccine development, and epidemiology. A total of 150 questions were answered by experts in the field providing a comprehensive and practical overview of COVID-19 and allergic disease.
Keywords: pandemie; Hypersensitivity; allergy; coronavirus disease 2019; COVID-19; lidé; SARS-CoV-2; Pandemics; Pneumonia, Viral; severe acute respiratory syndrome-related coronavirus 2; koronavirové infekce; alergie; Coronavirus Infections; Humans; virová pneumonie; Betacoronavirus